Karakteristik Marshall Penggunaan Slag Sebagai Penambah Agregat Kasar Pada Campuran Asphalt Concrete Binder Course (AC-BC) - Cahyadi, Lutfi; Suratmin, Suratmin; Ravi, Ahmad (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2023)
Asphalt concrete is one type of bending pavement that is commonly used in Indonesia. Asphalt concrete is a layer on highway construction consisting of a mixture of hard asphalt and aggregates that well graded, mixed, spread and compacted in hot state at a certain temperature. In this study, aggregate substitute materials the rough used is waste from steel smelting (Slag). The utilization of Slag as a substitute for coarse aggregates can be reducing environmental problems due to Slag being included in waste B3 (Hazardous and Toxic Materials) and its huge amount. Purpose from this study is to find out the physical properties of Slag used as a substitute material for coarse aggregates and the influence of the use of Slag against Marshall's characteristics in the AC-BC mixture. In this study Slag is used as a coarse aggregate enhancer material in AC-BC (Asphalt Concrete-Binder Course) mixture with asphalt content obtained from the optimum asphalt content of 6% and Slag used is 10% and 20%. The results of this study show that slag cannot be used as a coarse aggregate enhancing agent. The influence on Marshall's characteristics is also seen from the lower stability values of the normal mixture. For VFA, VIM, VMA, Flow and MQ values indicate that do not meet the specification